Simulation of induction motor / Ahmad Nazri Alwi - Alwi, Ahmad Nazri (1990)
The simulation is based on the two-axis theory of the alternating current machines, i.e the general theory of alternating current machines. The traditional method used for the analysis of electrical machine is in the steady state condition, this is contributed by the fact that calculation on the dynamic behaviour was closed to impossible, hence it is very difficult to predict system capability in supplying additional machines without major modification. The two-axis theory embodied in the generalised theory of electrical machines leads for both the steady state and transient performance of the three-phase machines. The mathematical analysis of the transient process requires the solution of differential equations and the methods used have invariably been based on a circuit analysis approach, which avoids detai1ed reference to the electromagnetic phenomena internal to the machines. The mathematics required include numerical few other methods.